Dynamics of Special Autonomy Implementation in Papua: Policy Analysis and Socio-Economic Impact - Salmawati Salmawati; Miryam Diana Kalagison; Halizah Asywhara (Universitas KH. Abdul Chalim Mojokerto, 2025)
The enactment of Law No. 21/2001 on Special Autonomy (Otsus) for Papua Province marked the state's effort to give greater authority to regions to manage development according to the local context. However, after more than two decades of implementation, this policy has not been able to significantly address the social and economic inequalities faced by the Papuan people. The main problem in this study is how much influence the implementation of the Special Autonomy Policy has on the socio-economic conditions of the Papuan people, as well as the relationship between the allocation of Special Autonomy funds and socio-economic indicators. The purpose of this study is to quantitatively measure the effect of the Special Autonomy Fund on socio-economic indicators and the relationship related to the effectiveness of this policy. The method used is a quantitative approach with descriptive and inferential statistical analysis, such as linear regression and normality tests, based on primary data from community surveys and secondary data from official documents and publications. The results of the correlation test showed a positive and significant relationship between the Special Autonomy Fund (Dana Otsus) variable and the Socio-Economic Impact variable. The Pearson correlation coefficient of 0.560 indicates a relationship that is at a moderate level and is positive in nature, which means that an increase in the allocation of the Special Autonomy Fund tends to be followed by an increase in the socio-economic indicators of the community and Based on the results of the Model Summary in linear regression analysis, a correlation coefficient (R) value of 0.560 was obtained which indicates a moderate positive relationship between the Special Autonomy Fund variable (Dana Otsus).These findings confirm the importance of transparent and participatory fund management and highlight the need to increase the capacity of local governments. Practically, this research can serve as a basis for developing more effective and sustainable policies in Papua.